2016
DOI: 10.1016/j.physleta.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Tricritical behaviour of the frustrated Ising antiferromagnet on the honeycomb lattice

Abstract: We use the effective-field theory with correlations based on different cluster sizes to investigate phase diagrams of the frustrated Ising antiferromagnet on the honeycomb lattice with isotropic interactions of the strength J 1 < 0 between nearestneighbour pairs and J 2 < 0 between next-nearest neighbour pairs of spins. We present results for the ground-state energy as a function of the frustration parameter R = J 2 /|J 1 |. We find that the cluster-size has a considerable effect on the existence and location … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…However, it is worth to note that the order-disorder phase transitions at g = 2/3 still take place at finite temperature, in agreement with recent findings for the model [1,2]. It means that the effects of frustration on the bcc lattice are weaker when compared to those found for the frustrated square and honeycomb lattices, in which antiferromagnetic second-neighbour interactions can bring the ordering temperature to zero [6,7,[25][26][27][28]. A possible explanation for this reduced sensitivity to frustration can be related to the higher dimensionality of the bcc lattice, which leads to long-range orders that are more robust under thermal fluctuations even when second-neighbour couplings introduce frustration.…”
Section: Resultssupporting
confidence: 85%
“…However, it is worth to note that the order-disorder phase transitions at g = 2/3 still take place at finite temperature, in agreement with recent findings for the model [1,2]. It means that the effects of frustration on the bcc lattice are weaker when compared to those found for the frustrated square and honeycomb lattices, in which antiferromagnetic second-neighbour interactions can bring the ordering temperature to zero [6,7,[25][26][27][28]. A possible explanation for this reduced sensitivity to frustration can be related to the higher dimensionality of the bcc lattice, which leads to long-range orders that are more robust under thermal fluctuations even when second-neighbour couplings introduce frustration.…”
Section: Resultssupporting
confidence: 85%
“…Another interesting open question is the existence and nature of the phase transitions in this model for R < −1/4. Unlike on the square lattice, the EFT found no LRO [27] but our recent MC study suggested a phase transition to a highly degenerate state consisting of frozen domains with the stripe-type AF ordering inside the domains separated by zero-energy domain walls [28]. A phase transition for R < −1/4 was very recently reported also by using the machine learning technique [30], however, the nature of the transition remains elusive.…”
Section: Discussionmentioning
confidence: 86%
“…One can notice that for R = −0.22 the pair of the curves splits in the vicinity of the expected transition temperature (anomalous decrease) and for R < −0.22 the temperature-decreasing curves do not join the temperature-increasing ones at low temperatures but rather follow different trajectories. In such a case, the energy corresponding of the temperature-decreasing branch is always higher and never reaches the expected ground-state value e GS = −3(2R + 1)/2 [27], denoted by the blackframed right-pointing triangles at T = 0. Therefore, apparently, in the temperaturedecreasing processes the system gets trapped in some rather stable, nevertheless, only metastable states.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations